The Meta_Body Project - Sousa, Catarina Carneiro de (2022)
Meta_Body is a project first held in online virtual environment and in a “real life” art exhibition, and now carrying on in the metaverse creative flux. The project addresses two aspects — the constitution of virtual corporality and the shared creative process of avatar building, sharing, transformation and embodiment.